Generation of a MYL3 knockout stem cell line (WAe009-A-1H) by episomal vector-based CRISPR/Cas9 system - Rui Bai; Wei Fu; Xiaojie Hou; Juyi Wan (Stem Cell Research)
The Myosin light chain 3 (MYL3) gene encodes the ventricular essential light chain isoform, which is an important modulator of sarcomeric myosin cross-bridge kinetics. Variants in MYL3 are a cause of hypertrophic cardiomyopathy and dilated cardiomyopathy with cardiac failure and sudden cardiac death (SCD). To further elucidate the involvement of MYL3 in the pathogenesis of cardiomyopathies, we have created a MYL3 knockout human embryonic stem cell line using the CRISPR/Cas9 system. Notably, this MYL3-knockout cell line retains normal morphology, pluripotency, and karyotype. This resource provides a valuable tool for investigating MYL3-related health and disease.